Macrophage migration inhibitory factor enhances Pseudomonas aeruginosa biofilm formation, potentially contributing to cystic fibrosis pathogenesis. Issue 11 (2nd August 2017) - Tynan, Aisling; Mawhinney, Leona; Armstrong, Michelle E.; O'Reilly, Ciaran; Kennedy, Sarah; Caraher, Emma; Jülicher, Karen; O'Dwyer, David; Maher, Lewena; Schaffer, Kirsten; Fabre, Aurelie; McKone, Edward F.; et al.
Abstract : Macrophage migration inhibitory factor (MIF) is a key proinflammatory mediator that we have previously shown to be associated with an aggressive clinical phenotype in cystic fibrosis. It possesses unique tauto‐merase enzymatic activity. However, to date, no human‐derived substrate has been identified that has the capacity to interact with this cytokine's unique tautomerase activity. This led us to hypothesize that MIF may have the capacity to interact with external substrates. We describe for the first time how Pseudomonas aeruginosa can utilize human recombinant MIF (rMIF) to significantly ( P < 0.01) enhance its endogenous biofilm formation. Our in vivo studies demonstrate that utilizing a small‐molecular‐weight inhibitor targeting MIF's tautomerase activity (SCD‐19) significantly reduces the inflammatory response in a murine pulmonary chronic P. aeruginosa model. In addition, we show that in in vitro experiments, pretreatment of P. aeruginosa with rMIF is associated with reduced bacterial killing by tobramycin. Our novel findings support the concept of an anti‐MIF strategy that targets this enzymatic activity as a potential future antibacterial therapeutic approach.—Tynan, A., Mawhinney, L., Armstrong, M. E., O'Reilly, C., Kennedy, S., Caraher, E., Jülicher, K., O'Dwyer, D., Maher, L., Schaffer, K., Fabre, A., McKone, E.F., Leng, L., Bucala, R., Bernhagen, J., Cooke, G., Donnelly, S. C. Macrophage migration inhibitory factor enhances Pseudomonas aeruginosa biofilm formation, potentially contributing to cystic fibrosis pathogenesis. FASEB J. 31, 5102–5110 (2017). www.fasebj.org